IDENTIFIKASI VARIAN SOMAKLONAL TOLERAN KEKERINGAN PADA POPULASI JAGUNG HASIL SELEKSI IN VITRO DENGAN PEG - Kaswan Badami; Achmad Amzeri (Agrovigor, 2011)
Main constraints ofcornproduction increasedareondrymarginalcornareasthathavelowproductivity. Droughtis one ofthecornproductionconstraints. Droughtatanystageof corngrowthgreatly affectscropproductivity. Increasedmaizeproduction canbe solvedbyusingdrought tolerant varieties.  The purposeofthis studywas to determinethe responseof hailsomaklonaR1 plantsin vitro selection result againstdrought stressandevaluate thephysiologicalcharacteristicsof droughttolerantplantssomaklon. The results showedthat (1) drought stressonthe reproductive phasecaused a decrease number ofseeds, dry weight of seed,cob, root and stemand(2) droughttolerantsomaclonalvarianthave higherprolineaccumulationthansensitive variantsomaclonal, but there is nocorrelationbetweendroughttolerancesomaclonalvariantplantswitha totalsugaraccumulation.